An analysis of nursing students' decision‐making in teams during simulations of acute patient deterioration. (5th June 2016) - Bucknall, Tracey K.; Forbes, Helen; Phillips, Nicole M.; Hewitt, Nicky A.; Cooper, Simon; Bogossian, Fiona; ,
Abstract: Aim: The aim of this study was to examine the decision‐making of nursing students during team based simulations on patient deterioration to determine the sources of information, the types of decisions made and the influences underpinning their decisions. Background: Missed, misinterpreted or mismanaged physiological signs of deterioration in hospitalized patients lead to costly serious adverse events. Not surprisingly, an increased focus on clinical education and graduate nurse work readiness has resulted. Design: A descriptive exploratory design. Methods: Clinical simulation laboratories in three Australian universities were used to run team based simulations with a patient actor. A convenience sample of 97 final‐year nursing students completed simulations, with three students forming a team. Four teams from each university were randomly selected for detailed analysis. Cued recall during video review of team based simulation exercises to elicit descriptions of individual and team based decision‐making and reflections on performance were audio‐recorded post simulation (2012) and transcribed. Results: Students recalled 11 types of decisions, including: information seeking; patient assessment; diagnostic; intervention/treatment; evaluation; escalation; prediction; planning; collaboration; communication and reflective. Patient distress, uncertainty and a lack of knowledge were frequently recalled influences on decisions. Conclusions: Incomplete information, premature diagnosis and a failure to consider alternatives when caring for patients is likely to lead to poor quality decisions. All health professionals have a responsibility in recognizing and responding to clinical deterioration within their scope of practice. A typology of nursing students' decision‐making in teams, in this context, highlights the importance of individual knowledge, leadership and communication.